The roles of clinical audit and test sets in promoting the quality of breast screening: a scoping review. Issue 10 (October 2020) - Qenam, B.A.; Li, T.; Tapia, K.; Brennan, P.C.
Abstract : Breast screening programmes enhance the probability of early breast cancer detection in many countries worldwide; however, the success of these efforts is highly dependent on the ability of breast screen readers to detect abnormalities in the screened population, which has low prevalence. Therefore, this task can be challenging. Clinical audit is a key quality assurance measure that aims to keep the screen reading performance within acceptable standards. Auditing, nonetheless, is a lengthy process, and its accuracy is dependent on available clinical data, which often can be limited. Mammographic standardised test sets are a different screen reading evaluation approach that provides participants with instant feedback based on a simulated environment. Although a test set provides unique evaluative qualities, its ability to represent clinical performance is debated. This article describes the distinctive roles of clinical audit and test sets in measuring and improving the quality of breast screening and highlights the relationship between test sets and clinical performance.